Factors Influencing the Acceptance of Metaverse Technology in Teaching Islamic Sciences (Hadith and Prophetic Biography as a Model) in Light of the UTAUT2 Model - Zekhnini, Sabah; Alnakawa, Mohamad (Millah: Journal of Religious Studies, 2026)
This study enhances the developing dialogue on immersive technology in Islamic higher education by investigating the factors influencing metaverse acceptability in the instruction of Hadith and the Prophetic Biography, utilizing the Unified Theory of acceptability and Use of Technology (UTAUT2). This study examines the impact of performance expectancies, perceived ease of use, institutional support, motivation, hedonic enjoyment, and demographic variables on Sharia-informed digital pedagogy, while offering ethically based implementation instructions to address a significant vacuum in the field. The study used a quantitative descriptive-analytical design. An online survey was used to gather information from (201) Al Qasimia University staff and students (out of a total population of 300) during the second semester of the 2025–2026 school year. Partial Least Squares Structural Equation Modelling (PLS-SEM) was used in the UTAUT2 framework to examine structural relationships. The findings show that while enabling environments improve implementation, behavioural intention is highly predicted by motivation, perceived ease of use, and performance expectancy. Differences by gender and age were statistically significant. The findings contribute theoretically by contextualizing UTAUT2 within Islamic pedagogical environments and practically by outlining culturally and religiously responsive design principles. The paper offers an empirically supported paradigm for the ethical and Sharia-compliant incorporation of metaverse technology into Islamic sciences curricula at the university level.